The Negative Mirror and Critical Memory - Paul Armstrong (Oz, 1990)
Marco Polo's negative mirror is, more or less, like one of the concave parabolic surfaces used to concentrate the parallel solar rays into a unique point, giving them a previously unknown shining. In a similar manner the traveler's gaze will bend the apparently isolated and undifferentiated facets of a place and tie them together in a more intense reality thereby revealing the "genius loci," which is a projection of human conscience.